Flexural Design of Reinforced Concrete Frames Using a Genetic Algorithm - Camp, Charles V; Pezeshk, Shahram; Hansson, Håkan (Journal of structural engineering (New York, N.Y.), 2003)
A design procedure implementing a genetic algorithm is developed for discrete optimization of reinforced concrete frames (RC-GA). The design procedure conforms to the American Concrete Institute (ACI) Building Code and Commentary. The objective of the RC-GA procedure is to minimize the material and construction costs of reinforced concrete structural elements subjected to serviceability and strength requirements described by the ACI Code. Examples are presented demonstrating the efficiency of the RC-GA procedure for the flexural design of simply-supported beams, uniaxial columns, and multi-story frames.